Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.ufug.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Contested construction of nature for city fringe outdoor recreation in southern Sweden: The Arrie case

Abstract: IntroductionThis study deals with the process of change from industrial to recreational land use on a 60 ha piece of land. The site called Lake Arrie is situated 12 km southeast of Malmö in southernSweden (see Fig. 1). The lake, covering more than a third of the area, has originated from an abandoned gravel quarry in the midst of an agricultural landscape. It is argued that the case study of Arrie illustrates several general aspects of contemporary changes of land use in the contested city fringe. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Both recreation and food are to a large extent connected to ideas of romantic and utilitarian aspects of outdoor life with close ties to urbanity, (male) gender, (middle) class and national identity in Sweden and other countries in the global north (e.g. Cronon 1996 ; Satterfield et al 2013 ; Lisberg Jensen and Ouis 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both recreation and food are to a large extent connected to ideas of romantic and utilitarian aspects of outdoor life with close ties to urbanity, (male) gender, (middle) class and national identity in Sweden and other countries in the global north (e.g. Cronon 1996 ; Satterfield et al 2013 ; Lisberg Jensen and Ouis 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This view can be questioned and debated. In a study of outdoor recreation, Lisberg-Jensen and Oius (2008) found that the implicit norms and values of outdoor recreation that were used as means for extra-Scandinavian migrants to integrate into Swedish society were problematic. Nakagawa & Payne (2011) discuss the problems of belonging and the cultural construction of place identity in their study of international students' experience of ‘the beach’ in Victoria.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural/attitudinal accessibility. There is ample research on how different ethnic groups -usually minorities -perceive and use different PA environments (Rishbeth, 2001;Morris, 2003;Lisberg et al, 2008;Gentin, 2011;Byrne 2012). More broadly, this dimension can be understood as relating to all equality in the sense of taking into account diversity; for example, religion, bodily composition, sexual orientation or gender should not affect the use of PA environments.…”
Section: Kontula Skatepark In Helsinkimentioning
confidence: 99%